PROJECT-BASED LEARNING IN SECONDARY LANGUAGE CLASSROOMS: IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH COLLABORATIVE ORAL PROJECTS - Juliati Juliati; Helminsyah Helminsyah (SENSEI RESEARCH CENTER, 2023)
Speaking remains one of the most challenging skills for secondary school students learning English as a foreign language because it requires fluency, accuracy, pronunciation, vocabulary control, confidence, and interactional competence. Conventional speaking instruction often relies on dialogue memorization, teacher-led questioning, and short oral drills, which provide limited opportunities for authentic communication. This study aims to examine the effectiveness of project-based learning in improving students’ speaking skills in secondary language classrooms and to explore students’ learning experiences during project implementation. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group design supported by classroom observations, interviews, and reflective journals. The participants were 70 Grade IX students divided into an experimental group and a control group. The experimental group learned speaking through project-based activities involving topic selection, group investigation, script development, rehearsal, oral presentation, peer feedback, and reflection. The control group received conventional speaking instruction. Quantitative data were collected through speaking performance tests and analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, and effect size analysis. Qualitative data were analyzed thematically. The findings showed that the experimental group achieved significantly higher speaking improvement than the control group. Students’ fluency, vocabulary use, interaction, and confidence improved through repeated practice, collaborative preparation, authentic project tasks, and peer-supported feedback. The study concludes that project-based learning can improve secondary students’ speaking skills when projects are structured, language-focused, collaborative, and supported by clear assessment criteria.